Fatal accidents among elite mountaineers: A historical perspective from the European Alps - Weinbruch, S.; Nordby, K.-C. (High Altitude Medicine & Biology, 2010)
The lifetime risk of a fatal mountain accident among elite European alpine mountaineers and its time trends are determined by studying a fixed cohort of 390 elite mountaineers listed in the Encyclopaedia of the Alps (Hiebler, 1977). At publication of the encyclopaedia, 158 individuals were still living and were followed up until the end of 2008. The crude lifetime risk of a fatal accident for elite mountaineers is 0.203 [95% confidence interval (CI), 0.165 to 0.246). The difference in mortality between male (0.207; 95% CI: 0.168 to 0.251) and female mountaineers (0.118; 95% CI: 0.033 to 0.343) is not statistically significant. No fatal accidents occurred among elite mountaineers born before 1820. For the birth cohort from 1820 to 1949, the lifetime risk of a fatal accident (male mountaineers only) increased with time from 0.069 (95% CI, 0.019 to 0.220) to 0.375 (95% CI, 0.212 to 0.573). For all time strata, the highest risk of a fatal mountain accident was observed at an age of 30 to 39yr. The high mortality among elite mountaineers clearly demonstrates that the limits of human performance are reached by these activities. The high risks should be communicated and should motivate risk-reduction efforts for this highly exposed subgroup of mountaineers.